EKRANISASI AWAL: BRINGING NOVELS TO THE SILVER SCREEN IN THE DUTCH EAST INDIES - , CHRISTOPHER ALLEN WOODRICH, Prof. Dr. Faruk, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study discusses the social act of adapting films from novels, as found in the Dutch East Indies, where this phenomenon began in 1927 with the adaptation of Eulis Atjih by G. Krugers and ended in 1942âbefore the Japanese occupationâwith the adaptation of Siti Noerbaja by Lie Tek Swie. The adaptation process from this period is little understood, yet important for understanding the history of screen adaptations, which are quickly becoming the most lucrative type of film in Indonesia. As such, this research was conducted in order to better understand the origins of this phenomenon and the earliest considerations in making the social act. This study uses Weberâs concept of the social act, a rational action conducted by an individual in order to interact with society and reach a certain goal. Data used is predominantly from primary and secondary sources. Primary sources used include contemporary newspapers and novels that were adapted to film (keeping in mind that the films themselves are lost), whereas secondary sources used include journals, articles, books, and the internet. A total of eleven films were adapted from eight novels in the Indies. Only one author had multiple works adapted, and two novels were adapted more than once. The nine producers and directors involved in adapting novels came from a variety of ethnicities. The works adapted, meanwhile, were generally popular in wide societyâ though often best known through stage performances and adaptations. During the period covered, the Indies was a colony in flux. Greater access to education meant that the financial elite were increasingly literate, leading to a growth in the literary industry. The lower class, meanwhile, was highly fond of stage performancesâoral literature for the illiterate which often loosely adapted famous novels. The film industry itself was attempting to find a successful formula, and in its early years faced heavy competition from the theatre. Educated women called for greater womenâs rights and protection of womenâs welfare, changes which began to be implemented in the 1940s. Meanwhile, after the Great Depression the economy began to transform from one based on the production of raw goods to one based in manufacturing. The rationalization process behind ekranisasi was a highly practical one, oriented not towards the creative adaptation of a creative work, but the exploitation of popular works to reach wider audiences, with modifications to take advantage of the medium and shifts in societal mores. Filmmakers were familiar with the predominantly oral nature of their audience, and thus consistently drew on works which had previously been adapted to the stage â and thus reaching wider audiences than the original novels. Further selection criteria included the popularity of a work, its position in relation to the different races in the Indies â particularly the target audience â and themes. Ultimately, ekranisasi was an instrumental act, influenced more by the need to achieve a profit than individual creative concerns by filmmakers. However, in later years works adapted from novels were, financially and critically, indistinct from works based on original stories.